A Multiparty Videoconferencing System Over an Application-Level Multicast Protocol - Wang, Wei; Luo, Chong; Tang, Jian; Sun, Jun; Li, Jiang (IEEE Transactions on Multimedia, 2007)
Increased speeds of PCs and networks have made media communications possible on the Internet. Today, the need for desktop videoconferencing is experiencing robust growth in both business and consumer markets. However, the synchronous delivery of high-volume media content is still a big challenge under a current heterogeneous Internet environment. In this paper, we present a multiparty videoconferencing system based on a peer-to-peer (P2P) solution. The contribution of our paper is twofold. On the one hand, we design an application-level multicast scheme which intends to tolerate the heterogeneity in videoconferencing applications. Design tradeoffs are analyzed and our decisions are made based on extensive experimentation. On the other, we design a five-layer architecture for implementing a multiparty videoconferencing system. This architecture makes a clear-cut distinction between different functional modules and therefore provides rich flexibility in feature adaptation. We believe that our work can be a helpful reference in other efforts on building desktop videoconferencing systems.